2020
DOI: 10.1097/ta.0000000000002953
|View full text |Cite
|
Sign up to set email alerts
|

Mean arterial pressure maintenance following spinal cord injury: Does meeting the target matter?

Abstract: INTRODUCTION Neurosurgical guidelines recommend maintaining mean arterial pressure (MAP) between 85 and 90 mm Hg following acute spinal cord injury (SCI). In our hospital, SCI patients receive orders for MAP targeting for 72 hours following admission, but it is unclear how often the patient’s MAP meets the target and whether or not this affects outcome. We hypothesized that the proportion of MAP measurements ≥85 mm Hg would be associated with neurologic recovery. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…Additional specific high-priority questions for further study include the role of prehospital BP management, the role of spinal perfusion pressure management (rather than systemic pressure), and the role of BP management in pediatric patients. Although blood pressure augmentation has been commonly performed for years, there is remarkably little high-quality data to support its use 43–46 . This topic has been debated for years and is sorely in need of high-quality studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional specific high-priority questions for further study include the role of prehospital BP management, the role of spinal perfusion pressure management (rather than systemic pressure), and the role of BP management in pediatric patients. Although blood pressure augmentation has been commonly performed for years, there is remarkably little high-quality data to support its use 43–46 . This topic has been debated for years and is sorely in need of high-quality studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although blood pressure augmentation has been commonly performed for years, there is remarkably little high-quality data to support its use. [43][44][45][46] This topic has been debated for years and is sorely in need of high-quality studies. One ongoing study of augmented systemic blood pressure in patients with acute SCI has had significant problems with recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…The unusual course, however, strongly emphasises the importance of spinal cord perfusion in the postinjury management of acute spinal cord injury. The favourable impact on spinal recovery of maintenance of cord perfusion is now well established2 3 although the evidence is mostly derived from human cohort and observational studies. Nevertheless, systematic reviews over the years4 5 have consistently reported a beneficial effect of blood pressure maintenance in spite of the absence of high-level studies.…”
Section: Discussionmentioning
confidence: 99%
“…Mean arterial pressure (MAP) is determined as systolic blood pressure (SBP) + [2 × Diastolic Blood Pressure (DBP)]/3. During the acute stage of SCI, it is recommended to maintain mean arterial pressure (MAP) of 85–90 mm hg for seven days by IV fluid resuscitation, inotropes and chronotropes as needed [ 2 , 5 , 7 ] Chronically, persons with high thoracic and cervical SCI may stabilize with baseline sitting SBP in the 90–110 mmHg range.…”
Section: Mechanism Of Sci: Emerging From Neurogenic Shockmentioning
confidence: 99%